Light‐Promoted Copper‐Catalyzed Enantioselective Alkylation of Azoles. (20th November 2020) - Li, Chen; Chen, Bin; Ma, Xiaodong; Mo, Xueling; Zhang, Guozhu
Abstract: A catalytic asymmetric alkylation of azoles with secondary 1‐arylalkyl bromides through direct C−H functionalization is reported. Under blue‐light photoexcitation, a copper(I)/carbazole‐based bisoxazoline (CbzBox) catalytic system exhibits good reactivity and high stereoselectivity, thus offering an efficient strategy for the construction of chiral alkyl azoles. These reactions proceed at low temperature and are compatible with a wide range of azoles. Abstract : A catalytic asymmetric alkylation of heteroaromatics, such as oxazoles and benzothiazoles, with secondary 1‐arylalkyl bromides through direct C−H functionalization is reported. Under blue‐light photoexcitation, a copper(I)/carbazole‐based bisoxazoline (CbzBox) catalytic system exhibits good reactivity and high stereoselectivity, thus offering an efficient strategy for the construction of chiral alkyl azoles.